Bioinformatic analysis of lucifensin potential as a nutraceutical source for livestock - Moh Mirza Nuryady; Diani Fatmawati; Kiky Martha Ariesaka; Inggita Utami; Rita Maliza; Ika Wahyuni (Universitas Sebelas Maret, 2022)
Objective: High number of antibiotic resistance cases in livestock will impact on increasing cases of microbe’s infection. On the other hand, the use of synthetic antibiotics is currently limited. A possible alternative can be used is the utilization of foods that possess medicinal effects (nutraceuticals). The use of animal feed sourced from Diptera larvae has been increasing widely, due to its high protein content. In addition, it is comprised of nutraceuticals as antimicrobial peptides like lucifensin. This study aimed at determining the potential of lucifensin as a nutraceutical product for livestock based on bioinformatics study.Methods: This study is descriptive research. The lucifensin protein data was obtained from the Protein Data Bank (PDB). The protein relationship analysis was performed using Blast-NCBI and lipinski Rules of 5 (Ro5) analysis to determine its potential as an oral drug (bioavailability). The molecular docking was used Swiss Docking online with lucifensin as target protein and Lipoteichoic Acid (LTAs) of Staphyllococus aureus as ligand.Results: The relationship analysis results showed that the lucifensin protein was related to two proteins of the other orders of diptera such as phormicin and sapecin. This protein belongs to the defensin protein family in which its coding genes are conserved until the order level. The Ro5 results showed that the mass of lucifensin protein was 312 daltons, its high lippopolycity was -0.5, it has five hydrogen bond donors, six hydrogen bond acceptors, and its molar refractivity was 77.14. Toxicity test also showed that this protein is classified as a safe component, and the docking results illustrate a strong energy bond that plays an important role in antimicrobial activity.Conclusions: In conclusion, lucifensin protein in the Lucilia sp. larvae is potential to be used as a livestock nutraceutical source that acts as an antimicrobial peptide.